KATA SERAPAN DALAM BAHASA JEPANG - Elizabeth Ika Hesti Aprilia Nindia Rini (Diponegoro University, 2018)
(Gairaigo) Loan word was born as a result of cultural and language contact with other countries. Loan word in Japanese or commonly known as gairaigo is known generally comes from English, but not entirely so. The purpose of this research is to describe the origin, form, and formation process of the loan word in Japanese, The method used is descriptive method. As the result of the research, it is found that Japanese loan word is not only from English; the form of loan word consists of 3 - 7 syllables; and entered into Japanese through adaptation and adoption process.Keywords: gairaigo, adaptation, adoption